Eksplorasi Integrasi Kearifan Lokal Aceh dalam Pembelajaran IPA untuk Mengembangkan Literasi Sains dan Kesadaran Lingkungan Siswa Sekolah Dasar - Lismarita Lismarita; Mahyuna Mahyuna; Deviyani Rusdiyanti Putri (Educational Journal, 2026)
This study aims to explore the integration of Acehnese local wisdom into elementary science learning to develop students’ scientific literacy and environmental awareness. The study employed a qualitative approach with an exploratory case study design. The research participants consisted of elementary school teachers and students selected purposively. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed through data condensation, data display, and conclusion drawing and verification. The findings indicate that Acehnese local wisdom, such as Hukum Adat Laôt, minyeuk pliek u, keumamah, jeungki, the use of local plants, and environmental management practices, can be integrated as meaningful sources and contexts for science learning. The integration process involved exploring students’ prior experiences, observing local phenomena, formulating scientific questions, reconstructing local knowledge through scientific concepts, conducting investigations, and reflecting on the learning process. These activities supported students’ ability to explain scientific phenomena, use evidence, connect science concepts with everyday life, and develop environmental care and responsibility. Acehnese local wisdom has strong potential to serve as a contextual, meaningful, culturally responsive, and sustainability-oriented resource for elementary science learning.